Farmakogenomik Hepatotoksisitas Obat Anti Tuberkulosis: [Hepatotoxicity Pharmacogenomic of Anti Tuberculosis Drugs] - Andri Dwi Wahyudi; Soedarsono Soedarsono (Faculty of Medicine Universitas Airlangga, 2015)
Anti-TB drugs (ATD) associated with hepatotoxicity is a serious medical problem in the world, especially for patients with TB. The production and expenditures toxic drug metabolites depends on the activity of some enzymes, such as N-acetyl transferase 2 (NAT2), Cytochrome P450 oxidase (CYP2E1) and Glutathione S-transferase (GSTM1). Variations from the DNA sequence or polymorphism at this locus (NAT2, CYP2E1 and GSTM1) can modulate enzyme activity and can affect the risk of hepatotoxicity. Hepatotoxicity is generally unpredictable and occur in a small number of patients even when the drug was given according to the recommended dosage. Among the ATD, the metabolism of INH, which is one of the ATD forefront, has been studied extensively, and said acetylation by NAT2, oxidation by cytochrome P450 oxidase (CYP2E1) and detoxified by GST play an important role in the INH-induced hepatotoxicity. Since the prevalence of polymorphisms is different in worldwide populations, the risk of ATD hepatotoxicity varies in the populations. Thus, the knowledge of polymorphisms at these loci, prior to medication, may be useful in evaluating risk and controlling ATD hepatotoxicity.